ÉDITER LES TEXTES DE THÉÂTRE EN LANGUE FRANÇAISE : APERÇU HISTORIQUE ET PERSPECTIVES. - PARUSSA, Gabriella (Médiévales)
This article offers a brief overview of editorial techniques which have been adopted to make medieval theatre texts, written in French, accessible to readers. The aim of this research, which focuses on editions published from the eighteenth century until today, is to present the key theoretical areas examined and provide concrete examples of techniques applied to theatre texts. The peculiarities of the transcription and the transmission of texts is bound to their performance, which, in turn, raises problems specific to the production of scholarly editions of these texts ; these speci- fic problems bring to light the weaknesses in the traditional methods. The article concludes by considering software tools and the on-line publishing of textual corpora in particular. This work underlines the considerable contributions it is making to the scholarly study of texts. It is time for a renewed reflection on transcription theories and on academic editorial practices.